PEMANFAATAN JAMUR ENTOMOPATOGEN Beauveria bassiana (Balsamo) Vuillemin TERHADAP LARVA Plutella xylostella (L.) DI LABORATORIUM - Akwila Prisilia Flira Aror; Ir. Caroulus S. Rante, MS.; Ir. Noni N. Wanta, MS. (COCOS, 2017)
ABSTRACT  The objective of research was to know the various concentrations of the fungus B. bassiana on the mortality P. xylostella larvae on cabbage plants in the laboratory.  This research used a Completely Randomized Design (CRD), which consisted of four treatments namely, A treatment (control) using sterile water (distilled), B treatment with B. bassiana spores concentration of 106 per ml, C treatment with a concentration of spores of B. bassiana 107 per ml, and D treatment with B. bassiana spores concentration of 108 per ml. Each treatment was repeated four times. Each test using 20 individual larvae as larvae test. Planting cabbage and decision larvae test is done by collecting a number of larvae P. xylostella of cabbage centers are not sprayed with pesticides in Tomohon.  Larvae were used as test is instar larvae of three. The data were analyzed using analysis of variance. If the treatment shows the real effect then continued by Least Significant Difference (LSD).  The results showed that B. bassiana fungus proved effective at killing larvae P. xylostella with the average concentration of the highest mortality in the treatment of 106 is 65.00%, respectively while the lowest concentration found in the treatment of 107 and 108 which respectively by 58.75% and 55.00%.  Keywords : Beauveria Bassiana, Plutella xylostella, Entomopatogen